1995
DOI: 10.1159/000227451
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with Tegafur and Low Dose Oral Leucovorin: A Dose-Finding Study

Abstract: Tegafur is an effective oral fluoropyrimidine that shows the same activity as 5-fluorouracil for a similar spectrum of cancers. Their biochemical modulation with oral Leucovorin (LV) attempts to simulate treatment with a continuous infusion of 5-fluorouracil and LV with the added advantage of outpatient administration. Thirty-three patients with advanced adenocarcinoma were included in the study. The treatment consisted of tegafur, 0.75 g/m2/day, for 21 days, with oral LV at different dose levels, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…To ameliorate emesis and nephrotoxicity, cisplatin at 100 mg/m 2 triweekly was modified to 50 mg/m 2 biweekly, and to ameliorate stomatitis and maintain efficacy, 5-fluorouracil (5-FU) at 1000 mg/m 2 /d through 120-h infusion was replaced with daily oral 5-FU prodrugs (tegafur 800 mg/d or tegafur-uracil at 300 mg/m 2 /d) [12] . According to a dose-finding study investigating toxicity, oral leucovorin at 60 mg/d was used in combination with tegafur for protracted treatment [13] . PUL and PTL combinations had lesser toxicity, particularly for severe stomatitis (5%–7%), and stronger efficacy compared with PF in our patients [14] , [15] .…”
mentioning
confidence: 99%
“…To ameliorate emesis and nephrotoxicity, cisplatin at 100 mg/m 2 triweekly was modified to 50 mg/m 2 biweekly, and to ameliorate stomatitis and maintain efficacy, 5-fluorouracil (5-FU) at 1000 mg/m 2 /d through 120-h infusion was replaced with daily oral 5-FU prodrugs (tegafur 800 mg/d or tegafur-uracil at 300 mg/m 2 /d) [12] . According to a dose-finding study investigating toxicity, oral leucovorin at 60 mg/d was used in combination with tegafur for protracted treatment [13] . PUL and PTL combinations had lesser toxicity, particularly for severe stomatitis (5%–7%), and stronger efficacy compared with PF in our patients [14] , [15] .…”
mentioning
confidence: 99%
“…21 To combine with tegafur for protracted treatment, a dose‐finding study for toxicity indicated a dose of oral LV in the range of 45–60 mg per day. 22…”
mentioning
confidence: 99%
“…Controlled studies in patients with advanced colorectal cancer showed that FT 1 g/m 2 /day for 21 days had a similar antitumour effi cacy to intravenous 5-FU [7]. In a phase I study, our group investigated the biochemical modulation of FT with oral levofolinic acid (LV) [8]. This combination attempts to simulate the continuous infusion of 5-FU and LV, with the advantage of an ambulant oral treatment.…”
Section: Introductionmentioning
confidence: 99%